SOCIAL SIGNIFICANCE OF ACCOUNTING. (The Accounting Review, 1931)
This article focuses on the editor's views about the social significance of accounting. Accounting is utilized as one means of exercising social control, that is, control by the government or by governmental agencies over institutions touched with a public interest. The right to inspect the accounts of private business enterprises is illustrative of this point. Bank examining is organized in the public interest, the audits being made for the protection of the depositors. Through the field audits of the U.S. Income Tax Bureau and the Bureau's accounting regulations, the federal government exercises an indirect control over numerous accounting policies. Another illustration is found in the power to prescribe uniform accounts. Usually one is inclined to relate the purpose of bookkeeping and accounting to the individual business enterprise. But here is a plain indication that the effect of poor bookkeeping extends far beyond the individual. Good bookkeeping, it seems, must be of some concern to society since the lack of it is so definitely associated with the great losses which attend bankruptcies.